aspifsGak5u

Answered

2022-01-03

where

I put the equation into the form

Answer & Explanation

ramirezhereva

Expert

2022-01-04Added 28 answers

Starting from $R=\sqrt{66},a=\mathrm{arcsin}\frac{7}{\sqrt{65}}$ we have

$\sqrt{65}\mathrm{sin}(x+a)=6$

$\Rightarrow x=\mathrm{arcsin}\frac{6}{\sqrt{65}}-a=arcisn\frac{6}{\sqrt{65}}-\mathrm{arcsin}\frac{7}{\sqrt{65}}$

Using

$\mathrm{arcsin}u-\mathrm{arcsin}v=\mathrm{arcsin}(u\sqrt{1-{v}^{2}}-v\sqrt{1-{u}^{2}})$

$x=\mathrm{arcsin}(\frac{6}{\sqrt{65}}\cdot \frac{4}{\sqrt{65}}-\frac{7}{\sqrt{65}}\cdot \frac{\sqrt{65-{6}^{2}}}{\sqrt{65}})$

$x=\mathrm{arcsin}\left(\frac{24-7\sqrt{29}}{65}\right)$

Using

Vasquez

Expert

2022-01-08Added 457 answers

HINT:

NSK

The R is related to

so that

which is more convenient. Divide both sides by

where

Most Popular Questions